Infratentorial Pressure Monitoring in Cerebellar Stroke: Feasibility and Prognostic Utility - Won, Sae-Yeon; Herrmann, Eva; Neumeister, Anne; Hagemeier, Jonas; Dubinski, Daniel; Obada, Alhalabi T.; Behmanesh, Bedjan; Bernstock, Joshua D.; Freiman, Thomas M.; Lademann, Olaf; Rafaelian, Artem; Schewe, Jens-Christian; et al. (Neurocritical care, 2025)
Although supratentorial intracranial pressure (ICP) monitoring represents the current standard in neurocritical care, its validity for assessing infratentorial pathologies remains uncertain. This multicenter, prospective study aimd to (1) evaluate the feasibility and clinical utility of infratentorial ICP monitoring in acute posterior fossa pathologies and (2) develop a prognostic model for functional outcomes based on infratentorial pressure dynamics.
Gesehen am 13.02.2026